From genome to phenome: omics perspectives on fish reproduction - Mushtaq, Malik Wasim; Rather, Mohd Ashraf; Khan, Irfan Ahmad; Bhat, Hussna; Mir, Ishfaq Nazir; Bhat, Irfan Ahmad (Frontiers in Aquaculture, 2026)
Fish reproduction, a complex biological process, is regulated by diverse molecular, biochemical, and physiological mechanisms. Advances in omics technologies, including genomics, transcriptomics, metabolomics, and phenomics, have provided every possible way to understand the underlying pathways of reproductive development in fish. In contrast to conventional approaches, omics technologies give us a detailed, molecule-by-molecule view of how an organism’s energy, hormones, and metabolism change during its most important reproductive phases. Metabolomics and lipidomic studies in fish have revealed the importance of lipid and amino acid metabolism during embryogenesis and ovarian development, while transcriptomics and proteomics helped to identify key genes and proteins involved in steroidogenic pathway and reproductive development. Nutritional omics on the other hand highlights the role of essential fatty acids, in enhancing overall reproductive performance, so the offspring quality. Moreover, omics is transforming genetic conservation by providing a new toolkit to optimize the freezing process and ensure the long-term survival of genetic resources, securing a future for endangered fish germplasm. Together, these strategies do more than optimize aquaculture like, fortify conservation efforts, build sustainable and resilient futures for fish populations worldwide.